2014
DOI: 10.1007/s00423-014-1221-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of quality of life in patients with benign goiter after surgical treatment

Abstract: QoL in patients with benign thyroid diseases improves significantly after operative treatment, independent of the extent of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 27 publications
7
50
4
3
Order By: Relevance
“…A previous study that specifically analyzed the correlation between chronic asthenia and thyroidectomy found patients who had undergone TT frequently complained of tiredness or asthenia in performing physical tasks and mental work [12]. It is well known that hypothyroidism, hyperthyroidism, and Hashimoto's thyroiditis may be associated with chronic asthenia [39,42]. However, thyroid surgery itself does not improve QoL except for specific symptoms such as compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that specifically analyzed the correlation between chronic asthenia and thyroidectomy found patients who had undergone TT frequently complained of tiredness or asthenia in performing physical tasks and mental work [12]. It is well known that hypothyroidism, hyperthyroidism, and Hashimoto's thyroiditis may be associated with chronic asthenia [39,42]. However, thyroid surgery itself does not improve QoL except for specific symptoms such as compression.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue that could modify/influence both surgeon and patient choice in favor of a surgical option is the assessment of the QoL after thyroidectomy. Prior studies indicated that surgery extent does not influence the QoL [38] and the specific symptom Btiredness^remains one of the most affected domains [39][40][41] after thyroidectomy. It should be noted that in these studies both TT and HT are considered together.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies have used the ThyPRO questionnaire for investigating changes in QOL after thyroid surgery and, overall, some improvements were identified. However, limited statistical power, heterogeneous patient populations, and missing information on thyroid stimulating hormone (TSH) levels, makes it difficult to extrapolate the results to individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Понятно, что значительная часть пациентов, страдающих патологией щитовидной железы, нуж-даются в хирургическом лечении, и ввиду большой распространенности данной патологии важнейшей задачей современной хирургии становится улучше-ние качества жизни больных в послеоперационном периоде [5][6][7][8]. Очевидно, что основное внимание в этом вопросе приковано к предотвращению раз-вития таких тяжелых осложнений, как параличи гортани и послеоперационный гипопаратиреоз, ко-торые могут привести к инвалидизации пациента.…”
unclassified